Behavioral and Molecular Effects of Thapsigargin-Induced Brain ER- Stress: Encompassing Inflammation, MAPK, and Insulin Signaling Pathway - Sahar Askari; Pegah Javadpour; Fatemeh Sadat Rashidi; Leila Dargahi; Khosrow Kashfi; Rasoul Ghasemi (Life, 2022)
Accumulation of misfolded proteins, known as endoplasmic reticulum (ER) stress, is known to participate in Alzheimer’s disease (AD). AD is also correlated with impaired central insulin signaling. However, few studies have probed the relationship between memory, central ER stress, inflammation, hippocampal mitogen-activated protein kinase (MAPK) activity and insulin resistance. The present study aimed to investigate the causative role and underlying mechanisms of brain ER stress in memory impairment and develop a reliable animal model for ER-mediated memory loss. Thapsigargin (TG), a known ER stress activator, was centrally administered. The cognitive function of animals was evaluated by the Morris Water Maze (MWM). To verify the induction of central ER stress, we investigated the mRNA expression of UPR markers in the hippocampus. In addition, the activation of ER stress markers, including Bip, CHOP, and some related apoptosis and pro-inflammatory proteins, such as caspase-3, Bax, Bcl-2, TNF-α, MAPK, and insulin signaling markers, were assessed by Western-blots. The results demonstrated that TG impairs spatial cognition and hippocampal insulin signaling. Meanwhile, molecular results showed a concurrent increment of hippocampal UPR markers, apoptosis, P38 activity, and TNF-α. This study introduced TG-induced ER stress as a pharmacological model for memory impairment in rats and revealed some underlying mechanisms.